2016
DOI: 10.3390/molecules21091199
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Cytotoxic Activity on Human Cancer Cells of Novel Isoquinolinequinone–Amino Acid Derivatives

Abstract: A variety of aminoisoquinoline-5,8-quinones bearing α-amino acids moieties were synthesized from 3-methyl-4-methoxycarbonylisoquinoline-5,8-quinone and diverse L-and D-α-amino acid methyl esters. The members of the series were evaluated for their cytotoxic activity against normal and cancer cell lines by using the (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) (MTT) assay. From the current investigation, structure-activity relationships demonstrate that the location and structure of the amino a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 23 publications
3
12
0
Order By: Relevance
“…Recent studies from our research group (Bayrak et al, , ; Yildirim et al, ) and that of Ferreira (Dias et al ), Ryu (Ryu, Song, Lee, Hong, Yoon, & Kim, ; Ryu, Yoon, Song, Im, Kim, & Kim, ), Tandon (Tandon, Maurya, Kumar, Rashid, & Panda, ; Tandon et al, ), and Valderrama (Valderrama, Ibacache, Rodriguez, Theoduloz, & Benites, ; Valderrama, Leiva, Rodriguez, Theoduloz, & Schmeda‐Hirshmann, ) have shown that electrophilic character of 1,4‐quinones can undergo with neutral and/or anionic nucleophiles in different conditions in versatile reactions, thus leading to various biologically active (hetero)cyclic quinone structures for their pharmacological properties. In this regard, as a result of the immense value of quinone compounds in organic and medicinal chemistry, 1,4‐quinones have been studied for over a half‐century as an important class of building blocks and still continue to attract considerable attention due to the broad range of synthetic and medicinal applications (Bayrak et al, ; Johnson‐Ajinwo et al, ; Pingaew et al, ; Ravichandiran, Kannan, Ramasubbu, Muthusubramanian, & Samuel, ; Ravichandiran, Subramaniyan, et al, ; Tandon & Kumar, ; Valderrama et al, ; Wellington, ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies from our research group (Bayrak et al, , ; Yildirim et al, ) and that of Ferreira (Dias et al ), Ryu (Ryu, Song, Lee, Hong, Yoon, & Kim, ; Ryu, Yoon, Song, Im, Kim, & Kim, ), Tandon (Tandon, Maurya, Kumar, Rashid, & Panda, ; Tandon et al, ), and Valderrama (Valderrama, Ibacache, Rodriguez, Theoduloz, & Benites, ; Valderrama, Leiva, Rodriguez, Theoduloz, & Schmeda‐Hirshmann, ) have shown that electrophilic character of 1,4‐quinones can undergo with neutral and/or anionic nucleophiles in different conditions in versatile reactions, thus leading to various biologically active (hetero)cyclic quinone structures for their pharmacological properties. In this regard, as a result of the immense value of quinone compounds in organic and medicinal chemistry, 1,4‐quinones have been studied for over a half‐century as an important class of building blocks and still continue to attract considerable attention due to the broad range of synthetic and medicinal applications (Bayrak et al, ; Johnson‐Ajinwo et al, ; Pingaew et al, ; Ravichandiran, Kannan, Ramasubbu, Muthusubramanian, & Samuel, ; Ravichandiran, Subramaniyan, et al, ; Tandon & Kumar, ; Valderrama et al, ; Wellington, ).…”
Section: Introductionmentioning
confidence: 99%
“…A549 cells are epithelial cells and MRC-5 cells are fibroblastic cells. However, since normal epithelial cells are difficult to maintain and expand in culture, we selected this widely used normal cell line for our screening [11][12][13].…”
Section: Resultsmentioning
confidence: 99%
“…Unsap exerts a low toxicity (CC 50 = 59 ± 3.9 µg/mL) on WI-38 human lung fibroblast normal cells (Figure 3e). However, the selective index (the ratio between IC 50 value for normal fibroblast cells and IC 50 value for cancer cells) towards HepG-2, A-549 and Panc-1 was 2.63, 1.94 and 3.01, respectively, indicating high selective toxicity (≥ 2) against those cancer cells as reported by Valderrama et al, (2016). Squalene has a chemopreventive effect against colon carcinogenesis (Rao et al, 1998).…”
Section: Cytotoxic Activity Of Unsap Against Cancer Cell Linesmentioning
confidence: 87%